MENINGKATKAN HASIL BELAJAR PKn MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARNING DI KELAS IV SEKOLAH DASAR - Kamarudin Kamarudin; Irwan Irwan; Azaz Akbar; Herdianto Herdianto (Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Luwuk, 2023)
Citizenship Education is one of the subjects that can improve the quality of Human Resources, especially students. The learning process is a very important factor in the formation of good personality and individual behavior. The research objective is to improve Civics learning outcomes using the Contextual Teaching and Learning (CTL) model in grade IV SD Negeri 2 Taipabu. This type of research uses Classroom Action Research (PTK) which is carried out in stages starting from planning, implementing, observing, and reflecting. The results showed that in the implementation of the learning outcomes of students who had achieved the KKM in cycle I were 13 students (59.1%) and who had not reached the KKM were 9 students (40.9%) with an average score of 62, so that they continued to cycle II, because it has not yet reached the indicator of success. In cycle II there were 18 students (81.8%) and those who had not reached the KKM were 4 students (18.1%) with an average score of 74. It can be concluded that applying the Contextual Teaching and Learning (CTL) model can improve student learning outcomes in class IV SD Negeri 2 Taipabu